1998
DOI: 10.1117/12.324066
|View full text |Cite
|
Sign up to set email alerts
|

A hinged-pad test structure for sliding friction measurement in micromachining

Abstract: We describe the design, modeling, fabrication and initial testing of a new test structure ,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…However, it has been shown that relationship (10) does not hold at the microscale [9]. This discrepancy is due to the dependence of the engineering coefficient of friction on various attractive (adhesion) forces arising at the contact interface, which are not included in (6).…”
Section: A Static Friction Of Sidewall Contact Interfacesmentioning
confidence: 91%
See 2 more Smart Citations
“…However, it has been shown that relationship (10) does not hold at the microscale [9]. This discrepancy is due to the dependence of the engineering coefficient of friction on various attractive (adhesion) forces arising at the contact interface, which are not included in (6).…”
Section: A Static Friction Of Sidewall Contact Interfacesmentioning
confidence: 91%
“…According to traditional (macroscopic) friction theories (e.g., Coulomb friction), the interfacial shear strength varies linearly with the external contact pressure, i.e., (10) where is the conventional (engineering) coefficient of friction given by (6). However, it has been shown that relationship (10) does not hold at the microscale [9].…”
Section: A Static Friction Of Sidewall Contact Interfacesmentioning
confidence: 97%
See 1 more Smart Citation
“…Much of the early work on surface characterization and friction testing has been discussed by Komvopoulos [10]. Senft and Dugger [11] and de Boer et al [12] conducted friction and adhesion experiments using micromachined test structures. Flater et al [13] performed wear experiments with a surface micromachine that generated nanoscopic sliding at the contact interface.…”
Section: Introductionmentioning
confidence: 99%
“…From a model of the motion of the motor under the influence of electrical stimuli, the dynamic coefficient of friction can be calculated. De Boer et al [12,13] developed a dedicated friction measurement device that uses a cantilever beam bent by electrostatic actuation, causing a hinged pad to slide over a counter-surface. By monitoring the bending of the cantilever at a certain applied actuation voltage with an optical interferometer, they could measure the static coefficient of friction as a function of normal load.…”
Section: Mems Tribometersmentioning
confidence: 99%